2014
DOI: 10.1111/den.12332
|View full text |Cite
|
Sign up to set email alerts
|

Double‐balloon enteroscopy for choledochojejunal anastomotic stenosis after hepato‐biliary‐pancreatic operation

Abstract: Dilation of choledochojejunal anastomosis combined with stent deployment using DBE-ERCP seems to be a viable first-line treatment for patients with stenosis of choledochojejunal anastomosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…[61] The success rate of insertion into the bilioenteric anastomotic site for patients after Roux-en-Y reconstruction was unsatisfactory compared with that for patients after PD with Child resection. [62] In our analysis a low enteroscopy success rate did occur in the patient group who had bariatric RYGB surgery undergoing ERCP with short type DBE. However, a large multicenter study showed that the success rates of ERCP with various enteroscopes appear to be similar between RYGB and non-RYGB surgical anatomy.…”
Section: Discussionmentioning
confidence: 66%
“…[61] The success rate of insertion into the bilioenteric anastomotic site for patients after Roux-en-Y reconstruction was unsatisfactory compared with that for patients after PD with Child resection. [62] In our analysis a low enteroscopy success rate did occur in the patient group who had bariatric RYGB surgery undergoing ERCP with short type DBE. However, a large multicenter study showed that the success rates of ERCP with various enteroscopes appear to be similar between RYGB and non-RYGB surgical anatomy.…”
Section: Discussionmentioning
confidence: 66%
“…[4][5][6] Percutaneous transhepatic biliary drainage (PTBD) is the conventionally alternative method in patients who fail ERCP. In cases of failed cannulation in surgically altered anatomies, balloon enteroscopy-assisted ERCP is as an alternative that has shown high technical and clinical success in specialized centers; [10][11][12] however, currently, it is not a well-established procedure. [7][8][9] It may also be difficult to carry out when the intrahepatic bile ducts are not dilated.…”
Section: Introductionmentioning
confidence: 99%
“…The short double-balloon enteroscope (DBE) is considered a useful device for endoscopic retrograde cholangiopancreatography (ERCP) in patients with surgically altered anatomies 1. One reason for this is that the short length of the scope allows many conventional ERCP accessories to be used, unlike the long DBE.…”
Section: Introductionmentioning
confidence: 99%